Violation of the quantity principle in the conversation of the Diwan Balkh play - Mohammed, Aqeel AbdulHussein; Nemah, Aya Kazim (Al-Adab Journal, 2021)
Language is the medium of communication between people and pragmatics studies the used language, meaning the study of the writer or speaker’s intended meaning. The oldest definition of pragmatism is the one by Charles Morris which states: pragmatism is the study of the relationship between signs and the users of these signs. In (1975) Paul Grice gave his lecture at Harvard University in the form of an article titled (Logic and conversation) in which he stated his theory (The cooperative principle) on the bases of connection and understanding between the parties involved in the conversation. The first principle in this theory is the principle of quantity. Violation of this principle leads to the information being more or less than required. The violation of any of these principles leads conversational implications. This violation is in the form of ambiguity, exaggeration and metaphor … etc. In this research, we have considered pragmatism and its relationship with semantics, meaning and the theory of the principle of cooperation and its meaning alongside correction, speech analysis and a few examples of violating the quantity principle in the play of Diwan Balkh.